Genes & Genomics - Cho, Yoon Shin.; Chung, Yun Doo.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: The Genetics Society of Korea, co-published with Springer.)
Genes & Genomics is a bimonthly journal in genetics and genomics. It aims to disseminate the rapidly developing genetic information to the genetic community. The coverage extends from fundamental to molecular aspects of the heredity. The disciplines are Mendelian transmission genetics, cytogenetics, molecular genetics and biology, genomics, population genetics, and quantitative genetics.
Keywords: Human genetics; Microbial Genetics and Genomics; Plant Genetics and Genomics; Animal Genetics and Genomics; Human Genetics